فاعلية برنامج إرشادي لتدعيم نظام المناعة النفسية ومنع اضطرابات ما بعد الصدمة لدى أسر المصابين بمرض السرطان - حسن، هبة صلاح بشير (جامعة عين شمس - كلية التربية, 2021)
هدفت الدراسة إلى التعرف على أثر فاعلية برنامج إرشادي لتدعيم نظام المناعة النفسية ومنع اضطرابات ما بعد الصدمة لأسر مرضى السرطان، تكونت عينة الدراسة من (٦٠) فرد مصاب بمرض السرطان، حيث اعتمدت الدراسة على المنهج التجريبي لمناسبته لمثل هذه الدراسات، وذلك بالاعتماد على الأدوات التالية (البرنامج الإرشادي، مقياس المناعة النفسية، مقياس اضطرابات ما بعد الصدمة)، وبعد تحليل النتائج باستخدام الأساليب الإحصائية المناسبة لمتغيرات الدراسة أظهرت النتائج وجود فروق ذات دلالـة إحصائية بين متوسطات درجات المجموعة التجريبية ومتوسطات المجموعة الضابطة في القياس البعدي المباشر على مقياس المناعة النفسية و وجود ارتباط طردي قوي بين القياس القبلي والقياس البعدي للمجموعة التجريبية على البعد الأول بقيمة بلغت (0.881)، وبلغ المتوسط الحسابي للدرجات على الاختبار القبلي لبعد (البعد الأول) (20.54)، في حين ارتفع متوسط درجاتهم على الاختبار البعدي لبعد (البعد الأول) وبلغ (38.53)، وتوجد فروق ذات دلالة إحصائية بين متوسط درجات القياس القبلي والقياس البعدي للمجموعة التجريبية على مقياس المناعة النفسية لصالح التطبيق البعدي، توجد فروق ذات دلالة إحصائية بين متوسط درجات القياس القبلي والقياس البعدي للمجموعة التجريبية على مقياس أعراض اضطرابات ما بعد الصدمة لصالح التطبيق البعدي، بوجود ارتباط طردي قوي بين القياس القبلي والقياس البعدي للمجموعة التجريبية على البعد الثالث بقيمة بلغت (0.823)، وبلغ المتوسط الحسابي للدرجات على الاختبار القبلي لبعد (البعد الثالث) (29.36)، في حين ارتفع متوسط درجاتهم على الاختبار البعدي لبعد (البعد الثالث) وبلغ (46.73)، وقد خرجت الدراسة ببعض التوصيات أهمها استخدام أدوات الدراسة المتعلقة بكفاءة نظام المناعة النفسية في تشخيص الاضطرابات السلوكية والانفعالية، ومدى التكيف مع الواقع المضطرب وتعميم تطبيق البرنامج الإرشادي على عيادات الصحة النفسية كمدخل عالجي وقائي للمشكلات النفسية.
The study aimed to identify the impact of a guidance program to strengthen the mental immune system and prevent PTSD for families of cancer patients, the study sample was formed from (60) individuals with cancer, where the study relied on the experimental approach for such studies, based on the following tools (guidance program, psychological immunity measure , measure of post-traumatic stress disorder), and after analyzing the results using appropriate statistical methods for study variables the results showed differences of statistical indication between averages of Experimental group scores and averages of the group controlled in direct distance measurement on the psychological immunity measure and a strong ejection link between tribal and distance measurement of the experimental group on the first dimension with a value of (0.881), the mathematical average of grades on the tribal test of the dimension (first dimension) (20.54), while their average score on the distance test increased to (first dimension) and reached (38.53), There are statistically significant differences between the average tribal and distance measurement scores of the experimental group on psychological immunity measure in favor of remote application, there are statistically significant differences between the average tribal and distance measurement scores of the experimental group on the PTSD symptoms scale in favor of remote application. In the presence of a strong ejection link between tribal and distance measurement of the experimental group on the third dimension with a value of 0.823, the mathematical average of grades on the tribal test of the dimension (third dimension) (29.36), While their average score on the distance test increased to 46.73, the study made some recommendations, the most important of which was the use of study tools on the efficiency of the psychological immune system in diagnosing behavioral and emotional disorders, the extent to which they adapt to the turbulent reality, and the dissemination of the extension program to mental health clinics as a preventive high-level input for psychological problems.
Keywords: المناعة النفسية -- البرامج الارشادية -- الاضطرابات النفسية -- أسر المرضى -- مرضى السرطان